2022
DOI: 10.2147/jpr.s374433
|View full text |Cite
|
Sign up to set email alerts
|

The Focus and New Progress of Percutaneous Balloon Compression for the Treatment of Trigeminal Neuralgia

Abstract: Trigeminal neuralgia is a condition confined to the trigeminal nerve, causing one or more branches of facial nerve pain. Surgical treatment options for trigeminal neuralgia include microvascular decompression(MVD), percutaneous balloon compression (PBC), radiofrequency thermocoagulation(RF), percutaneous retrogasserian glycerol rhizotomy(PRGR), gamma knife, etc. Of these treatments, PBC is increasingly being used by clinicians for trigeminal neuralgia. PBC is a simple surgical operation performed to treat trig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…The most common complication after PBC is facial numbness, which is directly related to the success of the surgery and is an important indicator of su cient compression. Longer compression times are more effective for recurrent or refractory TN, but studies have not found that compression lasting longer than 5 minutes provides better pain relief, although facial numbness lasts longer [4]. Many scholars have analyzed the relationship between balloon compression time and postoperative facial numbness.…”
Section: Discussionmentioning
confidence: 99%
“…The most common complication after PBC is facial numbness, which is directly related to the success of the surgery and is an important indicator of su cient compression. Longer compression times are more effective for recurrent or refractory TN, but studies have not found that compression lasting longer than 5 minutes provides better pain relief, although facial numbness lasts longer [4]. Many scholars have analyzed the relationship between balloon compression time and postoperative facial numbness.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it carries complications like local tissue toxicity, burning alcohol neuritis, and fibrosis in the region. Other treatment modalities include microvascular decompression, balloon decompression [ 22 ], gamma knife surgery, or the Jannetta procedure. However, these are considered highly invasive, and patients are often reluctant to choose any of these options.…”
Section: Discussionmentioning
confidence: 99%
“…CT-guided percutaneous rhizotomy or neuro-navigation systems may facilitate needle placement and reduce the risk of complications in such cases ( Pérez-Bovet et al, 2022 ). Having an adequate anatomical localization is crucial during the procedure, as the puncture of unwanted neuro-vascular structures can result in various complications such as cranial nerve palsy, cerebrospinal fluid leak, bradycardia, carotid-cavernous fistula, intracranial hemorrhage, and others ( Xia et al, 2022 ) Meuwly et al, 2015 . The knowledge of the neuroanatomy and relationship of the foramen ovale is mandatory in avoiding these complications.…”
Section: Discussionmentioning
confidence: 99%